Bid‘ah and Its Implementaton on Wahhabi’s Concept - Noor Rohmad, Rudik; Ritonga, A. Husein; Al-Munawwar, S. Sagap (Center for Religious Studies and Social Empowerment Foundation, 2024)
This article discusses the concept of heresy from the Wahhabi perspective who live in Jambi. The main problem is how Wahhabis conceptualize and implement bid‘ah in their worship practices. This article comes from qualitative research with a phenomenological approach. Data collection was carried out through observations made at several mosques used for activities. The data sources in this research are library data consisting of books, books, journals and field data obtained from observations. The results of the research show that for Wahhabis, bid‘ah is making things up or creating new things in worship that have never been prescribed. For Wahhabis, what is called worship must have a determined type, number, procedure and time. However, not all worship that did not exist during the time of the Prophet or was never exemplified by the Prophet can be called heretical. Artikel ini membahas tentang konsep bid‘ah perspektif Wahhabi yang berdomisili di Jambi. Permasalahan utamanya adalah bagaimana Wahhabi mengkonsepsikan dan mengimplementasikan bid‘ah dalam praktik ibadah mereka. Artikel ini berasal dari penelitian kualitatif dengan pendekatan fenomenologi. Pengumpulan data dilakukan dengan observasi yang dilakukan di beberapa masjid yang digunakan untuk kegiatan. Adapun sumber data dalam penelitian ini adalah data kepustakaan yang terdiri dari Kitab, buku, journal, dan data lapangan yang diperoleh dari observasi. Hasil penelitian menunjukkan bahwa bagi Wahhabi, bid‘ah adalah mengada-ada atau membuat hal baru dalam ibadah yang tidak pernah disyari’atkan. Bagi Wahhabi, yang disebut ibadah pastilah sudah ditentukan jenisnya, bilangannya, tata caranya, dan waktunya. Namun demikian, tidak semua ibadah yang tidak ada pada zaman Nabi ataupun tidak pernah dicontohkan oleh Nabi bisa disebut sebagai sesat.